Sustainable development or survival of Macau? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | In June of this year, a publication entitled ‘Macau’s sustainability and diversification’ noted that Macau’s ‘economic volatility caused by an unbalanced industrial structure restricts the diversified development of society. Economic diversification is the only way for Macau to achieve sustainable development’. Nothing new there, and, anyway, such a singular view is unconvincing. What about other aspects of society? Diversity is not singular, and it requires inclusion.